Reversible Immobilization of Lipases on Heterofunctional Octyl-Amino Agarose Beads Prevents Enzyme Desorption - Nazzoly Rueda; Tiago Albuquerque; Rocio Bartolome-Cabrero; Laura Fernandez-Lopez; Rodrigo Torres; Claudia Ortiz; Jose Dos Santos; Oveimar Barbosa; Roberto Fernandez-Lafuente (Molecules, 2016)
Two different heterofunctional octyl-amino supports have been prepared using ethylenediamine and hexylendiamine (OCEDA and OCHDA) and utilized to immobilize five lipases (lipases A (CALA) and B (CALB) from Candida antarctica, lipases from Thermomyces lanuginosus (TLL), from Rhizomucor miehei (RML) and from Candida rugosa (CRL) and the phospholipase Lecitase Ultra (LU). Using pH 5 and 50 mM sodium acetate, the immobilizations proceeded via interfacial activation on the octyl layer, after some ionic bridges were established. These supports did not release enzyme when incubated at Triton X-100 concentrations that released all enzyme molecules from the octyl support. The octyl support produced significant enzyme hyperactivation, except for CALB. However, the activities of the immobilized enzymes were usually slightly higher using the new supports than the octyl ones. Thermal and solvent stabilities of LU and TLL were significantly improved compared to the OC counterparts, while in the other enzymes the stability decreased in most cases (depending on the pH value). As a general rule, OCEDA had lower negative effects on the stability of the immobilized enzymes than OCHDA and while in solvent inactivation the enzyme molecules remained attached to the support using the new supports and were released using monofunctional octyl supports, in thermal inactivations this only occurred in certain cases.